Graphene-based Li-ion hybrid supercapacitors with ultrahigh performance - Leng, Kai; Zhang, Fan; Zhang, Long; Zhang, Tengfei; Wu, Yingpeng; Lu, Yanhong; Huang, Yi; Chen, Yongsheng (Nano research, 2013)
There is a growing demand for hybrid supercapacitor systems to overcome the energy density limitation of existing-generation electric double layer capacitors （EDLCs）, leading to next generation-Ⅱ supercapacitors with minimum sacrifice in power density and cycle life. Here, an advanced graphene-based hybrid system, consisting of a graphene-inserted Li4Ti5O12 （LTO） composite anode （G-LTO） and a three-dimensional porous graphene-sucrose cathode, has been fabricated for the purpose of combining both the benefits of Li-ion batteries （energy source） and supercapacitors （power source）. Graphene-based materials play a vital role in both electrodes in respect of the high performance of the hybrid supercapacitor. For example, compared with the theoretical capacity of 175 mA-h.g-1 for pure LTO, the G-LTO nanocomposite delivered excellent reversible capacities of 207, 190, and 176 mA·1h·g-1 at rates of 0.3, 0.5, and 1 C, respectively, in the potential range 1.0-2.5 V vs. Li/Li＋; these are among the highest values for LTO-based nano- composites at the same rates and potential range. Based on this, an optimized hybrid supercapacitor was fabricated following the standard industry procedure; this displayed an ultrahigh energy density of 95 Wh·kg-1 at a rate of 0.4 C （2.5 h） over a wide voltage range （0-3 V）, and still retained an energy density of 32 Wh·kg-1 at a high rate of up to 100 C, equivalent to a full discharge in 36 s, which is exceptionally fast for hybrid supercapacitors. The excellent performance of this Li-ion hybrid supercapacitor indicates that graphene-based materials may indeed play a significant role in next-generation supercapacitors with excellent electrochemical performance.